Risk factors for candidemia mortality in hospitalized children - Fabio Araujo Motta; Libera Maria Dalla‐Costa; Marisol Dominguez Muro; Mariana Nadal Cardoso; Gledson Luiz Picharski; Gregory Jaeger; Marion Burger (Brazilian Society of Pediatrics, 2017)
Objective: To evaluate risk factors associated with death due to bloodstream infection caused by Candida spp in pediatric patients and evaluate the resistance to the main anti‐fungal used in clinical practice. Methods: This is a cross‐sectional, observational, analytical study with retrospective collection that included 65 hospitalized pediatric patients with bloodstream infection by Candida spp. A univariate analysis was performed to estimate the association between the characteristics of the candidemia patients and death. Results: The incidence of candidemia was 0.23 cases per 1000 patients/day, with a mortality rate of 32% (n = 21). Clinical outcomes such as sepsis and septic shock (p = 0.001), comorbidities such as acute renal insufficiency (p = 0.01), and risks such as mechanical ventilation (p = 0.02) and dialysis (p = 0.03) are associated with increased mortality in pediatric patients. The resistance and dose‐dependent susceptibility rates against fluconazole were 4.2% and 2.1%, respectively. No resistance to amphotericin B and echinocandin was identified. Conclusion: Data from this study suggest that sepsis and septic shock, acute renal insufficiency, and risks like mechanical ventilation and dialysis are associated with increased mortality in pediatric patients. The mortality among patients with candidemia is high, and there is no species difference in mortality rates. Regarding the resistance rates, it is important to emphasize the presence of low resistance in this series.